2016
DOI: 10.1002/psaq.12074
|View full text |Cite
|
Sign up to set email alerts
|

When Is Truth Relevant?

Abstract: The authors argue that the experience of knowing and having the truth about oneself known in the context of therapy is not an end in itself; rather, it is important because the trust engendered by this experience (epistemic trust or trust in new knowledge) opens one up to learning about one's social world and finding better ways to live in it. The authors consider the consequences of a lack of epistemic trust in terms of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 60 publications
0
13
0
3
Order By: Relevance
“…Camisasca et al, 2017;Giovanelli et al, 2020;Marchetti et al, 2020) and extending to subsequent, significant affective relationships (Bowlby, 1969(Bowlby, , 1973(Bowlby, , 1980. It has been suggested that children's decision to place trust in an unknown informant, especially in a context of uncertainty, may also depend on generalizing from their personal attachment history (Fonagy, 1998;Allison and Fonagy, 2016;Fonagy et al, 2019;see also, Bo et al, 2017;Luo et al, 2018). For example, securely attached children are more flexible in establishing trustful relationships with epistemically reliable strangers than children with a fragile relational past (see, for example, .…”
Section: Introductionmentioning
confidence: 99%
“…Camisasca et al, 2017;Giovanelli et al, 2020;Marchetti et al, 2020) and extending to subsequent, significant affective relationships (Bowlby, 1969(Bowlby, , 1973(Bowlby, , 1980. It has been suggested that children's decision to place trust in an unknown informant, especially in a context of uncertainty, may also depend on generalizing from their personal attachment history (Fonagy, 1998;Allison and Fonagy, 2016;Fonagy et al, 2019;see also, Bo et al, 2017;Luo et al, 2018). For example, securely attached children are more flexible in establishing trustful relationships with epistemically reliable strangers than children with a fragile relational past (see, for example, .…”
Section: Introductionmentioning
confidence: 99%
“…Consider the recurrent thread. Allison and Fonagy () write, “Fortunately, the overvaluation of insight is behind us, and the importance of emotional truth (the felt truth of an experience) seems generally recognized as the key to therapeutic progress” (p. 283). They characterize truth as a mental process rather than mental representation, a process that engenders “epistemic trust,” such that patients can begin to use social input.…”
Section: Discussionmentioning
confidence: 99%
“…So, any difference in outcome may just have been because of that reason, that is the patients felt safer and more nurtured which affected their representations of attachment relationships. One speculative explanation along these lines for this finding could be that the additional MBT‐based treatment fostered patients’ development of what has become known as ‘epistemic trust’, that is trust in the veracity of one's personal experience, which can be utilized therapeutically to enhance one's interpersonal skills and reduce vigilance and anxiety (Allison & Fonagy, ; Fonagy & Allison, ; Fonagy, Luyten, & Allison, ).…”
Section: Discussionmentioning
confidence: 99%